Bone Marrow Niche: Role of Different Cells in Bone Metastasis - Terhi J. Heino; Jorma A. Määttä (My University, 2025)
Purpose of Review
This report summarizes current knowledge of bone marrow hematopoietic stem cell (HSC) niche, focusing on the identification of niche cells and molecular mechanisms involved in HSC maintenance and bone metastasis.
Recent Findings
Novel imaging techniques are greatly improving our understanding of bone marrow niche and latest studies have revealed several complex multicellular regulatory mechanisms of niche function. Especially, the intriguing role of bone marrow macrophages and osteomacs is an emerging topic in the field. It appears that, e.g., macrophage polarization is important for communication with bone marrow stromal cells (BMSCs). Bone marrow is also a favorable environment for disseminated tumor cells and recent data shows that various niche cell types, including endothelial cells and BMSCs, regulate the progression of bone metastasis.
Summary
Bone marrow niche represents a multicellular system with complex interactions. Emerging data is providing us with a deeper understanding of this fascinating tissue and its role in metastasis.